Characteristics of primary splenic diffuse large B‐cell lymphoma and role of splenectomy in improving survival. Issue 17 (19th June 2015) - Bairey, Osnat; Shvidel, Lev; Perry, Chava; Dann, Eldad J.; Ruchlemer, Rosa; Tadmor, Tamar; Goldschmidt, Neta
Abstract : BACKGROUND: Primary splenic diffuse large B‐cell lymphoma (PS‐DLBCL), an uncommon type of non‐Hodgkin lymphoma, has been investigated only in small patient series before the rituximab era. The therapeutic role of splenectomy in addition to immunochemotherapy is unknown. METHODS: The databases of 7 medical centers in Israel were searched for patients diagnosed with PS‐DLBCL in 1982‐2013, and clinical, treatment, and outcome data were collected for 87 patients. The mean patient age was 59.6 years; 57.5% were male. RESULTS: Patients presented with abdominal pain (81%), B symptoms (59%), splenomegaly (84%), splenic masses (97%), and high lactate dehydrogenase (LDH) levels (84%); 61% had stage I or II disease. The diagnosis was made with core‐needle biopsy in 46 patients and with diagnostic splenectomy in 39 patients. Eighty patients (92%) were treated with cyclophosphamide, doxorubicin, vincristine, and prednisone; 68 (78%) received rituximab. A complete response was achieved in 67 patients (77%), and a partial response was achieved in 8 (9%). At 5 years, the overall survival (OS) rate was 77%, and the progression‐free survival (PFS) rate was 67%. When patients were stratified by splenectomy at diagnosis, the OS rates were 91% for splenectomized patients and 68% for nonsplenectomized patients ( P = .08), and the PFS rates were 85% and 55%, respectively ( P = .02). The respective values for the subgroup with early‐stage disease were 96% and 63% for OS ( P = .009) and 90% and 51% for PFS ( P = .01). In a multivariate analysis, a low Eastern Cooperative Oncology Group performance status and splenectomy independently predicted better PFS ( P < .03). CONCLUSIONS: Patients with PS‐DLBCL usually present with abdominal pain, high LDH levels, and a splenic mass. This study shows for the first time that splenectomy at diagnosis improves survival, specifically in patients with early‐stage disease. Cancer 2015;121:2909–2916. © 2015 American Cancer Society . Abstract : Primary splenic diffuse large B‐cell lymphoma generally presents with abdominal pain, high lactose dehydrogenase levels, and a splenic mass. Splenectomy at diagnosis improves progression‐free and overall survival for patients with early‐stage disease.